Intertwining worlds: The dynamics of linguistic religion and religious language - Mohammad, Ali Reza (Association for Scientific Computing Electrical and Engineering (ASCEE), 2024)
Linguists and scholars in Iran have overlooked the interaction between language and religion. The correlation between language and religion is substantial among individuals. This study aims to determine whether language serves religion or if there is a distinct category known as religious language. The purpose of this study is to explore further and analyze various perspectives on the relationship between language and religion. We devised a fundamental structure of conversation guidelines based on the works